PEDAGOGICAL TECHNOLOGIES IN THE MILITARY EDUCATION SYSTEM: MODERN APPROACHES AND INNOVATIVE DEVELOPMENT TRENDS (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes modern pedagogical technologies used in the military education system. The author highlights the role of innovative approaches such as interactive methods, artificial intelligence, virtual reality, simulation technologies, “Feedback” and “Reflection” mechanisms in enhancing the professional training and combat effectiveness of cadets. The article also examines the development prospects and problematic aspects of military pedagogy in the context of digital transformation.
Keywords: Military education, pedagogical technologies, innovative methods, artificial intelligence, virtual reality, simulation, interactive education, feedback, reflection, digital transformation.